Thymol Reduces Hepatorenal Oxidative Stress, Inflammation and Caspase-3#xd; Activation in Rats Exposed to Indomethacin. Issue 1 (31st December 2022) - Stephanie, Tijani Abiola; David, Olori O.; Farombi, Ebenezer O.
ABSTRACT: Indomethacin (IND) is a non-steroidal anti-inflammatory drug with many pharmacological benefits and multi-organ toxicities. Thymol (THY) is a natural phenolic monoterpenoid with many biological properties. However, there is scarcity of information on its potential on IND-induced hepatorenal damage in rats. This study investigated the effect of THY on IND-induced hepatorenal damage in rats. The four experimental groups contain control, IND alone (5 mg/kg), THY alone (250 mg/kg) and co-treated group that were treated orally for 21 consecutive days. Twenty four hour after treatments, rats were sacrificed and markers of hepatorenal damage (ALT, ALP, AST, G6PDH, GGT, BIL, CHOL, GLDH, LDH, MDH, SDH, creatinine, urea, uric acid, cystatin-C and electrolytes), antioxidant status markers, myeloperoxidase (MPO) activity, nitric oxide (NO), lipid peroxidation (LPO), tumor necrosis factor alpha (TNF-α), interleukin-1β (IL-1β) levels and caspase-3 activity were evaluated. IND increased hepatorenal toxicity, inflammatory and apoptotic markers and decreased antioxidant status. Co-administration of IND with THY significantly decreased hepatorenal damage biomarkers improved the antioxidant status and reduced the MPO activity, LPO, NO, TNF-α, IL-1β levels and caspase-3 activity in the liver and kidney of rats. In conclusion, THY mitigates against IND-induced oxidative stress, inflammation and caspase-3 activation in the liver and kidney of the rats.